34.5k views
5 votes
Which equation demonstrates the additive identity property?

© (7+41)+(7-4) = 14
(7+41+0 = 7+4;
(7+4)(1)= 7+41
© (7+41)+(-7-41 - 0

User Spassig
by
4.4k points

1 Answer

3 votes

Answer:

Explanation:

Solve for o in the equation (7 + 4) + (7 - 41) = 14©(7 + 4) + 0 = 7 + 41o(7 + 4)(1) = 7 + 41o(7 + 41) + ( - 7 - 41) = 0

We first need to simplify the expression removing parentheses

Simplify 41o(7 + 4): Distribute the 41o to each term in (7+4)

41o * 7 = (41 * 7)o = 287o 41o * 4 = (41 * 4)o = 164o

Our Total expanded term is 287o + 164o

Simplify 41o(7 + 41): Distribute the 41o to each term in (7+41)

41o * 7 = (41 * 7)o = 287o 41o * 41 = (41 * 41)o = 1681o

Our Total expanded term is 287o + 1681o

Our updated term to work with is (7 + 4) + (7 - 41) = 14©(7 + 4) + 0 = 7 + 287o + 164o(1) = 7 + 287o + 1681o + ( - 7 - 41) = 0

We first need to simplify the expression removing parentheses

Simplify 164o(1): Distribute the 164o to each term in (1)

164o * 1 = (164 * 1)o = 164o Our Total expanded term is 164o

Our updated term to work with is (7 + 4) + (7 - 41) = 14©(7 + 4) + 0 = 7 + 287o + 164o = 7 + 287o + 1681o + ( - 7 - 41) = 0

Step 1: Group variables: We need to group our variables (7 and 14©(7. To do that, we subtract 14©(7 from both sides (7 - 14©(7 = 14©(7 - 14©(7

Step 2: Cancel 14©(7 on the right side: 0o = 0 Step 3: Divide each side of the equation by 0

User OliJG
by
4.1k points